The Effect of Emotional Intelligence and Transformational Leadership on Innovative Work Behavior with Psychological Empowerment as a Variable Mediation - Diana, Linda Nur; Sudarma, Ketut (Management Analysis Journal, 2021)
The purpose of this study is to determine the effect of emotional intelligence and transformational leadership on innovative work behavior through psychological empowerment. The sample in this study were all employee of CV. Mubarokfood Cipta Delicia Kudus. The data collection method using a questionare and survey. The data analysis method used were Structure Equation Model- Partial Least Square (SEM-PLS) using the SmartPLS 3.0. The results showed that emotional intelligence has a significant positive relationship on innovative work behavior, however transformational leadership has a positive relationship but non significant on innovative work behavior. Emotional intelligence and transformational leadership have a positive significant on psychological empowerment. Psychological empowerment succesfully mediates the relationship between transformational leadership and innovative work behavior but fails to mediates the relationship between emotional intelligence and innovative work behavior. Future studies are expected to be able to take samples on different sector to generalize the results of research and develop variables that are able to as antecendent factor on innovative work behavior.